2000
DOI: 10.1097/00005344-200008000-00009
|View full text |Cite
|
Sign up to set email alerts
|

17??-Estradiol Increases Intracellular Calcium Concentration Through a Short-Term and Nongenomic Mechanism in Rat Vascular Endothelium in Culture

Abstract: 17Beta-estradiol (E2) plays an important role in Ca2+ fluxes in several cell types. It has been proposed that some of its effects are of nongenomic origin E2 at vascular smooth muscle level can block calcium entry through L-type calcium channels, this mechanism cannot include vascular endothelial cells (VECs), in which increases in the intracellular calcium concentration ([Ca2+]i) are necessary to NO synthesis. We used male rat aorta ECs in culture loaded with fura-2 and a fluorescence imaging system to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…Estradiol-BSA (E2-BSA) has been shown to elevate [Ca 2C ] i through non-genomic ERs in several cell models; for example, E2-BSA elevates [Ca 2C ] i in gonadotropin-releasing hormone-1 neurons (Temple & Wray 2005), human granulocytes (Stefano et al 2000a), and cultured human pre-osteoclastic cells (Fiorelli et al 1996). Fast calcium mobilization by E2-BSA has also been reported in rat aorta endothelial cells (Rubio-Gayosso et al 2000), as well as in thoracic and human arterial endothelia (Stefano et al 2000b). The observation that G-1, the GPR30 selective agonist (Bologa et al 2006), rapidly elevates [Ca 2C ] i in hypothalamic cells is consistent with a non-nuclear effect of estrogen.…”
Section: Discussionsupporting
confidence: 63%
“…Estradiol-BSA (E2-BSA) has been shown to elevate [Ca 2C ] i through non-genomic ERs in several cell models; for example, E2-BSA elevates [Ca 2C ] i in gonadotropin-releasing hormone-1 neurons (Temple & Wray 2005), human granulocytes (Stefano et al 2000a), and cultured human pre-osteoclastic cells (Fiorelli et al 1996). Fast calcium mobilization by E2-BSA has also been reported in rat aorta endothelial cells (Rubio-Gayosso et al 2000), as well as in thoracic and human arterial endothelia (Stefano et al 2000b). The observation that G-1, the GPR30 selective agonist (Bologa et al 2006), rapidly elevates [Ca 2C ] i in hypothalamic cells is consistent with a non-nuclear effect of estrogen.…”
Section: Discussionsupporting
confidence: 63%
“…Estrogen causes releases NO from arterial endothelial cells (11,44,47,60). Venous endothelial cells also synthesize and release NO, although in lower levels compared with arteries (38).…”
Section: Discussionmentioning
confidence: 99%
“…To assess estradiol direct effects on the sarcoplasmic reticulum, we added caffeine (an intracellular Ca 2ϩ releaser; 10 mM) (1,20) instead of phenylephrine, to contract aortic rings incubated in Ca 2ϩ -free solution. It has been shown that cyclopiazonic acid induces capacitative Ca 2ϩ entry through non-L-type Ca 2ϩ channels in rat aorta (16); hence, the ability of estradiol to interfere with such Ca 2ϩ entry was assessed by studying the effects of the hormone (pretreatment for 5 min) on the contractile response to cyclopiazonic acid (10 M) of aortic rings incubated in Ca 2ϩ -containing solution.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated changes in the intracellular Ca phenylephrine or the entry of extracellular Ca 2ϩ dependent on the depletion of the intracellular Ca 2ϩ stores. The fura-2 fluorescence response to the intracellular Ca 2ϩ concentration was calibrated as previously described (20).…”
Section: Methodsmentioning
confidence: 99%